Quand le syndrome Neerlandais: petrole, macroeconomie et forets au Gabon - Wunder, Sven (Center for International Forestry Research, 2003)
Gabon’s oil wealth coincides with the fact that it is one of the most forested countries in Africa; about four-fifths of its land area is covered by forests. But this is not really a coincidence. The central hypothesis of this report is that oil rents have enabled a series of pro-urban, anti-rural policies that, together with the low demographic pressure, have been key in protecting forests from degradation and deforestation. In particular, forest conversion to cropland has been contained. Most probably, oil has helped expand forest cover in absolute terms. This has occurred through a number of economy-wide market and policy responses to oil wealth. Yet, none of the policies has been implemented because the government cared particularly about forests. Rather, the policies accompanying oil wealth have caused agriculture to decline. This misfortune has enabled forests to expand by default. Gabon’s unintentional, ‘blind’ conservation policies have been far more successful in conserving forests than most of those designed consciously by governments that actively strive to protect their forests through direct conservation measures. The gradually emerging decline in Gabon’s oil revenues thus poses serious challenges both for the macroeconomy and for forest conservation. The final part of this report discusses development scenarios and specific policy options for how to adjust to declining oil rents without sacrificing Gabon’s rich forests.